Investigation of Vorticity during Prevalent Winter Precipitation in Iran - Iman Rousta; Farshad Javadizadeh; Fatemeh Dargahian; Haraldur Ólafsson; Amin Shiri-Karimvandi; Sayed Hossein Vahedinejad; Mehdi Doostkamian; Edgar Ricardo Monroy Vargas; Anayat Asadolahi (Advances in Meteorology)
In this study, precipitation data for 483 synoptic stations, and the U&V component of wind and HGT data for 4 atmospheric levels were respectively obtained from IRIMO and NCEP/NCAR databases (1961–2013). The precipitation threshold of 1 mm and a minimum prevalence of 50% were the criteria based on which the prevalent precipitation of Iran was identified. Then, vorticity of days corresponding to prevalent winter precipitation was calculated and, by performing cluster analysis, the representative days of vorticity were specified. The results showed that prevalent winter precipitation vorticity in Iran is related to the vorticity patterns of low pressure of Mediterranean-low pressure of Persian Gulf dual-core, low pressure closed of central Iran-high pressure of East Europe, Ural low pressure-Middle East High pressure, Saudi Arabia low pressure-Europe high pressure, and high-pressure belt of Siberia-low pressure of central Iran. At the same time, the most intense vorticity occurred when the climate of Iran was influenced by a massive belt pattern of Siberian high pressure-low pressure of central Iran. However, at the time of prevalent winter precipitation in Iran, an intense vorticity is drawn with the direction of Northeast and Northwest from the center of Iraq to the south of Iran.